Inflammation-Based Scores: A New Method for Patient-Targeted Strategies and Improved Perioperative Outcome in Cancer Patients. (26th April 2014) - Bugada, Dario; Allegri, Massimo; Lavand'homme, Patricia; De Kock, Marc; Fanelli, Guido
Abstract : Systemic inflammatory response (SIR) has actually been shown as an important prognostic factor associated with lower postoperative survival in several types of cancer. Thus, the challenge for physicians is to find specific, low-cost, and highlyreliable inflammatory markers, clearly correlated with prognosis and able to preoperatively stratify patient's risk. Inflammation is a promising target to improve perioperative outcome, and data show that anti-inflammation techniques have a great potential in the perioperative period of cancer surgery. Inflammation scores could be useful to stratify patients with a potential better response to anti-inflammation strategies. Furthermore, inflammation scores could prevent failure of clinical trials by a better definition of patients to be included in such trials; inflammation scoring could clarify the real role of different drugs and techniques on outcome after cancer surgery, defining if different therapies are required for different patients. The role of this review is to focus on the currently available scores, in order to clarify their rationale and to analyze the actual evidence and limits, providing physicians with an updated overview of the possible inflammation-based prognostic scores for cancer patients undergoing surgery.